Lexical variation in Philippine English: The case of deontic MUST and HAVE TO - Imperial, Rowland (My University, 2014)
This paper investigates the synchronic nature of lexical variation in the deontic modality system of Philippine English (PhE). Focusing on MUST and HAVE TO, grammatical and frequency analyses of spoken and written texts in PhE support the claim that modal auxiliaries are experiencing a decline in usage due to the rise of their corresponding quasi-modal forms (see Collins et al., 2014; Enriquez, 2012). Statistical analysis of internal (grammatical) and external (discourse-related) factors, however, suggests that the latter also significantly affects the variation in forms. Subsequently, two external, contact-induced influences were predicted to affect the variation phenomenon: the semantic mapping of Filipino overt politeness marking on English past-tense modals, and the lack of an intermediate semantic equivalent of HAVE TO in Filipino. Theoretical analysis of these factors suggests that the modality system of Filipino may be influencing the decline in usage of MUST and increase in viability of HAVE TO in expressing deontic meaning in PhE.
PUBLISHED
Keywords: Philippine English, World Englishes, modality, deontic modality, language variation and change; Identities in Transformation; Corpus Linguistics; LINGUISTICS; Philippine English; SOCIOLINGUISTICS; World Englishes; Education